Game as a Methodological Strategy in the Development of Social Skills for Leadership in Childhood - Azofeifa Lizano, Ana (2015)
This article is derived from a research which aimed at identifying the knowledge possessed by teachers of first cycle of a private school in Heredia about game as a methodological strategy for developing leadership skills in children. To record the systematization process, we designed a questionnaire of twelve questions. Also, the teachers’ trimestral plans were reviewed. Eight teachers participated in this research. The main results show that only four teachers use games in their classes, and that these are aimed at strengthening cognitive aspects. The findings indicated that although teachers reported the use of the game in their lessons, there is no evidence of methodological strategies in their planning or clarity in the domain of terms like leadership, leadership skills, and social skills.